2017
DOI: 10.15616/bsl.2017.23.4.339
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Kaempferol on Cultured Neuroglial Cells Damaged by Induction of Ischemia-like Condition

Abstract: This study was performed to evaluate the cytotoxicity induced by ischemia-like condition (ILC) in cultured neuroglial cells (C6 glioma cells). The protective effect of kaempferol (KAE), flavonoid against the cytotoxicity induced by ILC induction was assessed. In addition, antioxidative effects of KAE were done by colorimetric assays. Cell viability and the antioxidative effects such as DPPH-radical scavenging activity, superoxide dismutase (SOD)-like activity and inhibitory activity of lipid peroxidation (LP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Kaempferol, also known as kaempferol-3, is a flavonoid compound that belongs to an active ingredient of traditional Chinese medicine. It has been reported that the compound has many physiological functions [ 3 - 14 ] , including anti-inflammatory [ 3 , 4 ] and antitumor effects [ 5 - 7 ] and protection against organ ischemic injury [ 8 - 11 ] . In addition, the protective effect of kaempferol in myocardial IR injury has also been confirmed [ 9 , 11 ] , but the associated molecular mechanisms are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Kaempferol, also known as kaempferol-3, is a flavonoid compound that belongs to an active ingredient of traditional Chinese medicine. It has been reported that the compound has many physiological functions [ 3 - 14 ] , including anti-inflammatory [ 3 , 4 ] and antitumor effects [ 5 - 7 ] and protection against organ ischemic injury [ 8 - 11 ] . In addition, the protective effect of kaempferol in myocardial IR injury has also been confirmed [ 9 , 11 ] , but the associated molecular mechanisms are still unclear.…”
Section: Introductionmentioning
confidence: 99%